2021
DOI: 10.1002/jsfa.11034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of consumption of whole egg and egg fractions on cardiovascular disease factors in adult rats

Abstract: BACKGROUND While eggs are a low‐cost source of protein, rich in macro‐ and micronutrients, the association of egg intake and cardiovascular disease (CVD) remains controversial. This study investigated the effect of egg consumption on CVD parameters. Eggs were boiled, separated into four fractions (whole egg, 50% yolk‐reduced whole egg, egg yolk and egg white) and then freeze‐dried. The different egg fractions or distilled water (control) were orally gavaged to adult male Wistar rats at 1 g kg−1 rat body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The increased concentration of these kidney metabolites due to the normal range (0.4–0.8 mg/dl) did not affect the functioning of the kidney muscles (Baker et al, 1979 ; Salazar, 2014 ). It is concluded in some research that using whole egg and egg white did not affect kidney functions and its tissues (Chairuk et al, 2021 ; Saande et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The increased concentration of these kidney metabolites due to the normal range (0.4–0.8 mg/dl) did not affect the functioning of the kidney muscles (Baker et al, 1979 ; Salazar, 2014 ). It is concluded in some research that using whole egg and egg white did not affect kidney functions and its tissues (Chairuk et al, 2021 ; Saande et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…One group served as the control rats and was treated with tap water. The six other groups were treated with different egg preparations from the local or commercial layer chickens at a dosage of 10mg/g Body weight of rats adopting a protocol of Chairuk et al (2021) with some modifications. Details are shown in Table 1.…”
Section: Experimental Setup and Treatmentsmentioning
confidence: 99%
“…There are growing arguments on the chicken egg's probable contribution to cardiovascular risk factor incidences in consumers which drives the need for more studies in this area. While some studies associate chicken egg overconsumption with the possibility of cardiovascular risk factor occurrences (Rianne et al, 2001;Rouhani et al, 2018;McNamara 2000;Shim and Seo 2021); other authors report differently (Blesso 2015;Knopp et al, 1997;Chairuk 2021;Cassondra et al, 2019;DiMarco et al, 2017). One of the presumed risk factors associated with chicken egg overconsumption is viscera fat accumulation (viscera obesity) and hyperlipidemia (Dala et al, 2012, Shim andSeo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…86 Chairuk et al reported that intake of 1 (g/kg)/d of egg white decreased plasma cholesterol and body fat accumulation in Wistar rats. 91 This contradiction might be attributed to differences in species of experimental animals and calculation method of simulated egg white intake, which were often ignored. Zhu et al believed that the dosages of egg white used in past studies were too high to achieve in normal diets.…”
Section: Hypothesis That the Remaining Components In Eggs Regulate Ch...mentioning
confidence: 99%
“…The results of Zhu et al showed that the intake of one to five egg whites affected neither plasma nor liver cholesterol levels in hamsters . Chairuk et al reported that intake of 1 (g/kg)/d of egg white decreased plasma cholesterol and body fat accumulation in Wistar rats . This contradiction might be attributed to differences in species of experimental animals and calculation method of simulated egg white intake, which were often ignored.…”
Section: Hypothesis That the Remaining Components In Eggs Regulate Ch...mentioning
confidence: 99%